A multilayer MCTDH study on the full dimensional vibronic dynamics of naphthalene and anthracene cations - Meng, Qingyong; Meyer, Hans-Dieter (The journal of chemical physics, 2013)
Employing the multilayer multiconfiguration time-dependent Hartree (ML-MCTDH) method in conjunction with the multistate multimode vibronic coupling Hamiltonian model, we perform a full dimensional quantum dynamical study on the naphthalene (48D) and anthracene (66D) radical cations in their six lowest-lying doublet electronic states. For easily comparing results of full and reduced dimensionalities, MCTDH simulations based on larger sizes of primitive basis functions and single-particle functions than the previous ones [S. Ghanta, V. S. Reddy, and S. Mahapatra, Phys. Chem. Chem. Phys. 13, 14531 (2011)] https://doi.org/10.1039/c1cp21084j., are also performed. Extensive ML-MCTDH test calculations are performed to find appropriate ML separations of the wave functions (so-called ML-trees), and the convergence of the dynamical calculations are carefully checked. The ML-MCTDH method was developed for efficiently simulating quantum dynamics of large systems, and in fact the full dimensional ML-MCTDH calculations save a considerable amount of CPU-time in comparison with corresponding reduced dimensional MCTDH simulations. On basis of the present full and reduced dimensional simulations, the photoelectron (PE) spectra of these two cations are simulated and compared with corresponding experimental spectra. The agreement between theoretical and experimental PE spectra is good. Both full and reduced dimensional simulations give all main bands in the PE spectra. The vibronic energy-level positions from both ML-MCTDH and MCTDH calculations agree with corresponding experimental results. These quantum dynamical studies also complement the observations on diffuse interstellar bands with the wavelength of ∼7088, ∼6707, ∼6490, ∼6120, and ∼5959 Å measured by astronomers as well as laboratory experimentalists.